STUDIES ON THE TISSUE SPECIFICITY OF COLONY STIMULATING FACTOR (Journal of Sciences, Islamic Republic of Iran)
In this study granulocyte-macrophage colony stimulating factor (CSF) was prepared from rabbit and guinea pig lung tissues. The biological activity of these CSFs was measured on semisolid agar culture and compared with those of mouse and rat. Weight of animals, incubation time and cross-reactivity of CSFs with different bone marrow sources were also investigated. The results showed that both rabbit and guinea pig lung tissues produced and released CSF in the conditioned medium. The CSFs were active on ammonium chloride treated bone marrow cells from balblc mouse and on their own ammonium chloride treated bone marrow cells but could not stimulate the progenitor cells from other sources